Becoming Blue - Tarlow, Ellen; Chung, Julien (New York: NY Beach Lane Books, 2022)
Blue thinks being Red must be exciting since Red gets to fight fires and tell cars to stop, but when Blue tries being Red for the day he realizes the best thing to be is yourself.
new kids book 2025 spring.
Ages 0-8.
Grades K-1.
Keywords: Color -- Fiction; Individuality -- Fiction; Self-realization -- Fiction; Picture Book